The Unseen Lifecycle: The Role of Design in Preventing Unutilised Household Products - Isaksson, Vera; Wang, Junying (My University, 2024)
The United Nations has highlighted the urgent need for a sustainable lifestyle to address environmental degradation and resource depletion. Households play a critical role in achieving these goals by adopting more sustainable consumption behaviours. By researching the different parts of a product's journey, we can begin to understand how products become unutilised. This thesis explores the personal relationship people have with their products, aiming to find the underlying factors that contribute to products becoming unutilised. Through user studies, the research examined the trajectories of products moving within the household and how people's actions may lead to unutilised items. The project seeks to provide knowledge about why and how products become unutilised and will highlight different ways design can prevent products from becoming unutilised and contribute to creating sustainable consumption patterns. We present an activity system that focuses on how people, products and environment, i.e. the house, interact together. Within the system, tensions are formed between contradicting motives, activities, goals and outcomes. The result of the project is a concept portfolio with seven concepts that address different tensions within the system and illustrate how design can prevent products from becoming unutilised. Ultimately, this research contributes to the ongoing discourse on sustainable consumption and offers practical insights for designers seeking to promote the recirculation of products.
Keywords: vehicle-to-grid